Ethics in Finance, Financial Globalization and Stakeholder Responsibility: New Concept of Corporate Finance - Marantika, Abshor; Singh Rathod, Harishchandra; Chauhan, Rahul; Tria Putri, Librina; Maseleno, Andino (International Journal of Psychosocial Rehabilitation, 2020)
This article deals with the foundation of financial theory into corporate finance. Using analysis and synthesis scientific methods, and especially with the requirements for the successful application of these methods, in this article is not only review the financial literature but also it is shown the future approach of the expected financial paradigm. The aim of the paper is to describe and review financial theories in terms of classical, modern and actual approach; but also it is described the future approach of corporate finance in terms of financial function to establish the evolution and the cultural situation that affects the financial theories. This financial paradigm integrates ethics in finance, financial globalization, ICTs and stakeholder responsibility. The main result of this paper shows that it is necessary to take into consideration into financial paradigm aspects relate to the ethics, and concern to broad stakeholders interests to improve the efficiency of corporate finance that carry out the common good of the society.